From fragility to sustainability: Geoarchaeological investigations within the Maltese Archipelago. (20th October 2022) - Bennett, Jeremy; French, Charles; McLaughlin, Rowan; Stoddart, Simon; Malone, Caroline
Abstract: The Maltese Archipelago is a microcosm of long-term Anthropocene human manipulation of the environment spanning the last 8000 years. Despite their apparent fragility, the islands continue to sustain an increasing population. This paper summarises the geoarchaeological methods employed by the ERC-funded FRAGSUS Project and an associated PhD project which explored the terraced landscapes of these islands. Our projects employed archaeological excavation, sediment coring, palynology, soil survey, micromorphology, geochemistry, and absolute dating to obtain a new understanding of long-term landscape change. These scientific analyses are combined with historical data in the form of 19th Century land value assessments which offer new insights into folk concepts of agricultural viability. Landscape changes in the islands began with Neolithic agricultural activities from 5500 cal BC. These caused soil thinning which was further exacerbated by increasingly arid climatic conditions. Soil management strategies are then evident from the late 2nd millennium BC, persisting through medieval times, when the protection of red soils became enshrined in law, and into the present day, when agricultural terraces are the dominant landform in the rural landscape. The combined efforts of these projects exemplify the value of geoarchaeology in providing an environmental narrative that contextualizes the human history of landscapes. Our account of longue durée landscape use, abuse, and change is a fitting case history for the present state of the environment in Malta and beyond. Persistent development is now expanding urban sprawl into the managed, yet still fragile, rural landscape, resulting in a piecewise erasing of valuable historic agriscapes in the Mediterranean region.